2010
DOI: 10.1021/ma100259t
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity and Cooperative Motions of Cyclic Molecules in Partially Threaded Solid-State Polyrotaxanes

Abstract: We investigated the structure, thermal properties, and dynamics of polyrotaxane (PR), composed of poly(ethylene glycol) (PEG) and α-cyclodextrins (CDs), and PR derivatives comprising hydroxypropylated CDs, that is, hydroxypropylated PRs (HyPRs), in the solid state by using wide-angle X-ray scattering (WAXS), differential scanning calorimetry (DSC), and viscoelastic spectroscopy. It was observed that HyPRs with high chemical modification ratios show a WLF-type viscoelastic relaxation that can be ascribed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
4
43
0
Order By: Relevance
“…Since then, a lot of PRXs have been reported [22][23][24][25][26][27][28] . An elegant sliding network gel based on a PRX consisting of α-CyD and a PEG with long chain lengths was reported by Ito, et al and they described their physical properties in detail [29][30][31][32][33][34] . Hadziioannou, et al also reported similar sliding gels [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a lot of PRXs have been reported [22][23][24][25][26][27][28] . An elegant sliding network gel based on a PRX consisting of α-CyD and a PEG with long chain lengths was reported by Ito, et al and they described their physical properties in detail [29][30][31][32][33][34] . Hadziioannou, et al also reported similar sliding gels [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…the movement or rotation of the α-CD rings is rarely adopted for improving mechanical properties of bulk polymers, probably because the easy aggregation of α-CDs via hydrogen bonding between the abundant hydroxyl groups greatly reduces the mobility. [2,16] The situation has changed recently. A few elastomers crosslinked by modified polyrotaxane demonstrated that the pulley effect can also be realized in polymer networks in the absence of water.…”
Section: Doi: 101002/marc202000371mentioning
confidence: 99%
“…Nevertheless, the interesting pulley effect generated by the movement or rotation of the α‐CD rings is rarely adopted for improving mechanical properties of bulk polymers, probably because the easy aggregation of α‐CDs via hydrogen bonding between the abundant hydroxyl groups greatly reduces the mobility. [ 2,16 ]…”
Section: Figurementioning
confidence: 99%
“…This free mobility of threading CDs in PRXs is attractive for the development of functional supramolecular materials [46]. In PRX applications, chemical modification of the threading CDs is important to reduce intermolecular interactions of the PRXs, impart solubility in organic solvents and water, and introduce functional molecules [79]. In this regard, various methods of introducing functional groups at the threading CD moieties of PRXs are used.…”
Section: Introductionmentioning
confidence: 99%